Relationship Between Diabetes Distress and Quality of Life Among Patients with Type II Diabetes Mellitus - Yusran Haskas; Suarnianti Suarnianti; Erna Kadrianti (Poltekkes Kemenkes Palu, 2023)
Diabetes Mellitus or commonly abbreviated as DM is a chronic disease commonly found in Indonesia, especially among people in urban areas. It is known to be incurable during the sufferer's life span, so it is called a lifelong disease. Long-term Diabetes Mellitus has a psychological impact on the quality of life of patients. This study aims to determine the relationship between diabetes distress and quality of life among patients with type II Diabetes Mellitus in the work area of Tamanlanrea Jaya Community Health Center, Makassar. This was a quantitative analytical study with a cross sectional design. Study samples were selected using consecutive sampling technique which obtained a total sample of 82 patients. Data were collected using a questionnaire and analyzed using the Chi-square test. The results showed that there was a relationship between diabetes distress and quality of life among patients with type II diabetes mellitus with a ρ value of 0.012. It can be concluded that there was a relationship between diabetes distress and quality of life among patients with type II diabetes mellitus in the work area of Tamalanrea Jaya CHC, Makassar. Future researchers are recommended to involve a larger size of samples to determine additional elements that have an impact on the quality of life among people with diabetes mellitus.